Incentives to grow: multimarket firms and predation - Nitsche, Rainer (online, 2000)
Abstract:
urn:nbn:de:0168-ssoar-116263
Keywords: (stw)Potenzieller Wettbewerb; (stw)Verdrängungswettbewerb; (stw)Mehrproduktfertigung; (stw)Reputation; (stw)Spieltheorie; (stw)Markteintritt; (stw)Unternehmenswachstum; (stw)Glaubwürdigkeit; (stw)Theorie; (thesoz)multinationales Unternehmen; (thesoz)Netzwerk; (thesoz)Verdrängung; (thesoz)Strategie; (thesoz)Markterschließung; (thesoz)Wettbewerb; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Latente Konkurrenz; Verdrängungswettbewerb; Mehrproduktbetrieb; Mehrproduktfertigung; Prestige; Spieltheorie; Markteintrittsstrategie; Unternehmenswachstum; Glaubwürdigkeit; Theorie